Pengembangan Bahan Ajar Tematik Berbasis Kearifan Lokal Bagi Siswa Kelas IV Sekolah Dasar Negeri 13 Lonjengan Kecamatan Menjalin Kabupaten Landak Provinsi Kalimantan Barat - Fricilia Tika; Siti Halidjah; Dyoty Auliya Vilda Ghasya; Hamdani Hamdani; Asmayani Salimi (Journal on Education, 2023)
The research aims to produce thematic-based teaching materials local wisdom for fourth grade students at State Elementary School 13 Lonjengan District Establish Landak District, West Kalimantan Province. Types of research is a development research using the ADDIE model with Analysis, design, development, implementation and evaluation steps. Source quantitative research data in the form of material expert validation results, validation results media experts, and the results of filling out the practicality questionnaire of teaching materials by students and teachers.Qualitative data were obtained from notes, suggestions and comments from validators, students and Teacher. Research instruments in the form of interview guidelines, questionnaires and documentation.The feasibility level of teaching materials is validated by material experts an average of 3.7 with the category "Valid" with a level of feasibility of teaching materials validated to media experts obtaining an average of 4.2 in the category "Very valid”. The validation results by the two validators obtained an average recapitulation result of 3.9 with the "Valid" category so that the teaching material is feasible to be tested. The level of practicality of teaching materials for small-scale trials obtained an average of 4.2 in the "Practical" category and the level of practicality of teaching materials for scale trials large get an average of 4.4 with the category "Very Practical". Research result the practicality of teaching materials by teachers achieves an average of 4.1 in the "Practical" category.